Ироническая оценка советской действительности в творческой биографии Oлега Григорьева - Popiel-Machnicki, Wawrzyniec (Studia Rossica Posnaniensia, 2020)
This text is an attempt to acquaint the reader with the writer’s biography of Oleg Grigoryev, a Russian poet and a representative of “the literary underground”. His works can be classified as urban folklore. Most of his poems are full of harsh irony, which may shock with its dark humour. Grigoryev often resorts to the poetics of the absurd, which may lead a keen reader to the conclusion that he is close to the creative actions of the poetic group of the Oberiuty with Daniil Kharms and Alexander Vvedenski as their main representatives. In this light, Grigoryev’s poetry can be interpreted as a reflection of the dark Soviet reality in which he lived and with which he struggled. Such an attitude surely did not help him in succeeding within the official Russian literature.